A Survey of Herbal Usages Among Older Adults at Ban Don Hiang, Prachuap Khiri Khan - Inphiwas, Piyatida; Wanich, Poohwadol; Jayathavaj, Vadhana (Health Science Journal of Nakhon Ratchasima College, 2022)
The purpose of this research was to study the use of herbs in the elderly Ban Don Hiang, Prachuap Khiri Khan. The research instrument was the content validity assessment questionnaire by 3 qualified professors in Thai traditional medicine. The data were analyzed by quantitative method. The population used in the study were 1,553 older adults living in Ban Don Hiang, Koh Lhak sub-district, Muang Prachuap Khiri Khan district, Prachuap Khiri Khan Province. The sample size was determined using Taro Yamane formula, with the numbers of 132 people in total. The sample was selected by using purposive sampling. The data were analyzed by using computer software package. The statistics used for data analysis were frequency and percentage. The results were as follows: The elderly at Ban Don Hiang as many as 47 percent of herbs were used and can be classified by single herbs, drug formulas, and finished products as 31.1%, 2.3% and 9.1%, respectively. Herbs must be used with caution, that is, the right plant, the right part, the right portion, and the right disease.